A comparative study of glycopyrrolate and dexamethasone in the control of postoperative nausea and vomiting after intrathecal fentanyl and bupivacaine for caesarean section - Okonkwo, Ikemefuna P.; Onyekwulu, Fidelis A. (International Journal of Research in Medical Sciences, 2021)
Background: Postoperative nausea and vomiting (PONV) is an undesirable outcome that parturient who undergo caesarean section experience. We compare the efficacies of IV glycopyrrolate and IV dexamethasone as prophyaxis against PONV in these paturient. Methods: This was a prospective, randomized, double blind placebo-controlled study of seventy six (76) ASA II patients aged 18-40 years who underwent elective caesarean section under spinal anaesthesia. Patients were randomly allocated to three groups, group G (glycopyrrolate): n=26, group D (dexamethasone): n=25 and group C (control; normal saline): n=25. Data collection was with the aid of a proforma which included the biophysical profile, Belville scoring scale for PONV, Likert scale was used for patient satisfaction and side effects were also documented. The data were analyzed using SPSS version 17 and presented in tables and figures. Results: The demographic characteristics and mallampati scores of patients in all 3 groups were similar. The results showed that the incidence of PONV in group D was 8%, in group G 19.2% and in group C 32% (p= 0.048, OR= 0.185, 95% C.I for OR= 0.035 – 0.983). All patients expressed satisfaction in the care they received as assessed using the Likert scale and only patients who received IV glycopyrrolate experienced side effects in the form of dryness of the mouth. There were no side effects reported in patients who received IV dexamethasone. Conclusions: The study demonstrated that IV dexamethasone 8mg was more effective in controlling PONV after intrathecal fentanyl and bupivacaine for caesarean section when compared to 0.2 mg IV glycopyrrolate.